Enhancing Quality of Life Through the Advancement of Tourism Industry in Tegaren - Mijiarto, Joko; Adnyana, Made Bambang; Setiyowati, Arin; Nuryananda, Praja Firdaus (Future Science, 2023)
This article presents findings from a field study carried out in Tegaren, a popular tourism village located in Trenggalek. Tegaren has consistently ranked within the top 500 in the Anugerah Desa Wisata Indonesia for the past two years. As one of the standout tourist villages in Trenggalek, Tegaren boasts intriguing developments in its tourism sector, which piqued the researchers' interest. Utilizing a combination of interviews, observations, and a thorough review of relevant literature, the authors gathered data from various village officers. This collected information was then analyzed through qualitative research methods. To corroborate the findings, the authors also employed the TALC concept and the Better Life Index to measure the quality of life. Furthermore, an asset-based community development approach was applied to ensure the accuracy of the qualitative data. The article sheds light on the impact of the burgeoning tourism industry on specific Tegaren communities, namely besek farmers and homestay or lodging accommodation proprietors. Nevertheless, there remains ample room for further research and improvements in this study, which may be pursued in future investigations.